Design of Generalized Chebyshev Lowpass Filter with Defected Stripline Structure (DSS) - Zakaria, Z; Mutalib, M. A; Mohamad Isa, Mohd Sa'ari; Md Isa, A. A; Zainuddin, N. A; Sam , W. Y (2013)
This paper presents the design of generalized Chebyshev lowpass filter (LPF) and integrated with Defected Stripline Structure (DSS) using Suspended Stripline Structure (SSS). The study involves circuit analysis to determine generalized Chebyshev responses with a transmission zero at finite frequency in order to produce a reduced number of elements values of prototype circuit. The LPF provides a cut-off frequency at 6 GHz with a return loss better than -19 dB, while the DSS exhibits a notch at frequency of 3.2 GHz with a stopband response better than -40 dB. Thus, the integrated LPF and DSS will produce lowpass and band reject response simultaneously. The design is implemented on a Roger Duroid RO4350 with a thickness of 0.168 mm and dielectric constant, εr of 3.48. The simulation performance results show promising results that could be proved in the experiment works. This new class of integrated LPF and DSS would be useful in any RF/ microwave communication systems particularly in wideband applications where the reduction of overall physical volume, weight and cost is critical to maintaining its good performance.